Independent Auditor's Report (American Economic Review, 2014)
, 2024 on our consideration of the Foundation's internal control over financial reporting and on our tests of its compliance with certain provisions of laws, regulations, contracts and grant agreements and other matters. The purpose of that report is solely to describe the scope of our testing of internal control over financial reporting and compliance and the results of that testing